INTENSITY OF WORK TURNOVER JUDGING FROM THE LEADERSHIP STYLE AT THE UNIVERSITY SELAMAT SRI - Widodo, Putranto Hari; Hajar, Neli (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Purpose of this study was to determine the effect of transformational leadership on turnover intention, at Selamat Sri University. This research is an associative research, using quantitative methods and using the census method in determining the sample. Questionnaires were used as the main instrument of this study and data analysis used path analysis. The results showed that transformational leadership had a significant and negative effect on turnover intention. With a direct effect of 3 percent. And the indirect effect is 9 percent. The total influence of transformational leadership on turnover intention is 90 percent.